2021
DOI: 10.3390/w13192610
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Assessment of Groundwater Potential Using Geospatial Techniques in Southern Africa: A Case Study in the Zambezi River Basin

Abstract: Groundwater resources are largely used in rural communities of river basins due to their acceptable water quality and reliability for domestic purposes where little or no treatment is required. However, groundwater resources have been affected by changes in land use, mining activities, agricultural practices, industrial effluent, and urbanisation among anthropogenic influences while climate change impacts and volcanic eruptions have affected its involvement among the natural phenomena. The purpose of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Infiltration amount decreases when the terrain is steeper, and infiltration ratios are raised when the topography is plain. The amount of precipitation that percolates and reaches the aquifer highly depends on the slope's nature [22]. Most of the study area comprised plain to moderate slopes, with steep slopes representing only a small portion of the region.…”
Section: Slope and Drainage Densitymentioning
confidence: 99%
“…Infiltration amount decreases when the terrain is steeper, and infiltration ratios are raised when the topography is plain. The amount of precipitation that percolates and reaches the aquifer highly depends on the slope's nature [22]. Most of the study area comprised plain to moderate slopes, with steep slopes representing only a small portion of the region.…”
Section: Slope and Drainage Densitymentioning
confidence: 99%
“…Groundwater recharge and drainage density (DD) are complexly related and affected by various lithological structural factors [4,17]. Prior research has indicated that areas characterized by low drainage density are more prone to groundwater recharge [8,17], whereas other studies suggest that high drainage density constitutes a high potential for recharge [5].…”
Section: Preparation Of Groundwater-controlling Thematic Mapmentioning
confidence: 99%
“…Groundwater recharge and drainage density (DD) are complexly related and affected by various lithological structural factors [4,17]. Prior research has indicated that areas characterized by low drainage density are more prone to groundwater recharge [8,17], whereas other studies suggest that high drainage density constitutes a high potential for recharge [5]. In this study, the inverse connection between drainage density and groundwater was employed, where regions exhibiting very high DD imply rapid runoff and drainage from the area [17].…”
Section: Preparation Of Groundwater-controlling Thematic Mapmentioning
confidence: 99%
See 2 more Smart Citations